Muralidharan, Karthik. Accelerating India’s Development: A State-Led Roadmap for Effective Governance - Das, Jishnu (Journal of Economic Literature, 2025)
Jishnu Das of Georgetown University reviews “Accelerating India’s Development: A State-Led Roadmap for Effective Governance” by Karthik Muralidharan. The Econlit abstract of this book begins: “Explores ways of improving the functioning of Indian governance and accelerating its development, focusing on state-level governance and the delivery of public services.”